2014
DOI: 10.1038/cmi.2014.50
|View full text |Cite
|
Sign up to set email alerts
|

The activating effect of IFN-γ on monocytes/macrophages is regulated by the LIF–trophoblast–IL-10 axis via Stat1 inhibition and Stat3 activation

Abstract: Interferon gamma (IFN-c) and leukemia inhibitory factor (LIF) are key gestational factors that may differentially affect leukocyte function during gestation. Because IFN-c induces a pro-inflammatory phenotype in macrophages and because trophoblast cells are principal targets of LIF in the placenta, we investigated whether and how soluble factors from trophoblast cells regulate the effects of IFN-c on macrophage activation. IFN-c reduces macrophage motility, but enhances Stat1 activation, pro-inflammatory gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 73 publications
(146 reference statements)
4
43
0
Order By: Relevance
“…We also observed the regulation of a wide variety of genes encoding cell surface proteins by WTD treatment, including CD93 -a receptor critical for monocyte phagocytosis and CD44 and CD9 -markers involved in cell surface adhesion (Sup. Figure 5b); and an inhibition of type I IFN gene signature, in agreement with previous studies (Dallagi et al, 2015;Ito et al, 1999) (Sup. Figure 5b).…”
Section: Increased Il-10rβ Affinity Enhances Transcriptional Activitysupporting
confidence: 92%
“…We also observed the regulation of a wide variety of genes encoding cell surface proteins by WTD treatment, including CD93 -a receptor critical for monocyte phagocytosis and CD44 and CD9 -markers involved in cell surface adhesion (Sup. Figure 5b); and an inhibition of type I IFN gene signature, in agreement with previous studies (Dallagi et al, 2015;Ito et al, 1999) (Sup. Figure 5b).…”
Section: Increased Il-10rβ Affinity Enhances Transcriptional Activitysupporting
confidence: 92%
“…Functionally, IFN-γ also importantly contributes to the development of innate and adaptive immune responses, targeting mainly macrophages (36)(37)(38)(39) and T cells (40)(41)(42). IFN-γ signaling induces the expression of many transcription factors, that can amplify the IFN response (5).…”
Section: Type II Interferon (Ifn-ii)mentioning
confidence: 99%
“…They also form a major line of defence against invading pathogens in the decidua and thus protect the foetus from infection . In vitro studies have shown that dMϕ differentiation and polarization are regulated by factors produced by trophoblasts such as IL‐10, suppressing IFNγ‐induced Stat1 activation . During early gestation, dMϕ are also major producers of IL‐10 and are able to suppress and regulate the decidua immune response .…”
Section: Decidual Immune Cells and T Gondii Infectionmentioning
confidence: 99%